2017
DOI: 10.5194/acp-17-11673-2017
|View full text |Cite
|
Sign up to set email alerts
|

Role of atmospheric circulations in haze pollution in December 2016

Abstract: Abstract. In the east of China, recent haze pollution has been severe and damaging. In addition to anthropogenic emissions, atmospheric circulations and local meteorological conditions were conducive factors. The number of December haze days over North China and the Huanghuai area has increased sharply since 2010 and was greatest in 2016. During 2016, the most aggressive control measures for anthropogenic emissions were implemented from 16 to 21 December, but the most severe haze pollution still occurred, cove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
81
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 20 publications
9
81
1
Order By: Relevance
“…During the high air pollution days, the contours show a small ridge in the vicinity of the red positive cluster (Figure 3d), and the ridge in Russia disappears. Previous studies also found that the anticyclonic circulations have significant effects on the air quality in China Miao et al, 2017;Zhu et al, 2018) and that the Siberian high leads to reduced air pollution in North China Yin & Wang, 2017); our results are consistent with these studies. The U.S. networks exhibit similar results.…”
Section: Resultssupporting
confidence: 92%
“…During the high air pollution days, the contours show a small ridge in the vicinity of the red positive cluster (Figure 3d), and the ridge in Russia disappears. Previous studies also found that the anticyclonic circulations have significant effects on the air quality in China Miao et al, 2017;Zhu et al, 2018) and that the Siberian high leads to reduced air pollution in North China Yin & Wang, 2017); our results are consistent with these studies. The U.S. networks exhibit similar results.…”
Section: Resultssupporting
confidence: 92%
“…Air pollution is a particularly acute problem, as it affects the daily life of more than two-thirds of China's entire population (Liu andDiamond 2005, Zhang 2017). Winter haze has been choking citizens across major cities, such as the capital (Beijing), which has culminated during haze episodes in the winters of 2013, 2015 and 2016 (Zhang et al 2014, Zhu et al 2016, Yin and Wang 2017, Li et al 2018a. Severe haze leads to a sharp decrease in visibility, causing traffic hazards and disruptions, and, hence, affecting economic activities (Huang et al 2014, Chen and Wang 2015, Li et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the role of underlying climatic factors in modulating regional weather conditions in association with severe haze events has been reported and is expected to have influenced the change in the severity of haze (e.g., Niu et al, 2010;Wang et al, 2015;Cai et al, 2017;Yin and Wang, 2017;Zou et al, 2017). These climatic factors include a weakened EAWM system and the associated decreased nearsurface wind speeds (Niu et al, 2010) and increased relative humidity in the region , reduced Arctic sea ice and anomalous sea surface temperature (SST) in the subtropical western Pacific .…”
Section: Introductionmentioning
confidence: 99%
“…The observed negative trend of the EAWM during the past few decades has caused significantly reduced wind speeds over North China and subdued atmospheric transport of pollutants, and hence it has contributed to the increasing number of haze days (Niu et al, 2010;Huang et al, 2012;Li et al, 2016). The latest studies have analyzed the possible influences of anthropogenic climate change on haze occurrences (e.g., Cai et al, 2017;Yin and Wang, 2017;Zou et al, 2017). Based on historical and future climate simulations, Cai et al (2017) suggested that anthropogenic greenhouse gas emissions and the associated changes would increase the occurrences of weather conditions conducive to Beijing winter severe haze.…”
Section: Introductionmentioning
confidence: 99%